The onset of sleep disturbances and their associations with anxiety after acute high-altitude exposure at 3700 m - Bian, Shi-Zhu; Zhang, Laiping; Jin, Jun; Zhang, Ji-Hang; Li, Qian-Ning; Yu, Jie; Chen, Jian-Fei; Yu, Shi-Yong; Zhao, Xiao-Hui; Qin, Jun; Huang, Lan (Translational psychiatry, 2019)
Sleep disturbances and psychiatric repercussions pose great challenges at high altitude; however, few studies have investigated sleep disturbance and anxiety profiles and their associations after acute exposure in consecutive patients. Thus, we aimed to study the profiles of sleep disturbances in consecutive patients after high-altitude exposure and the association of such disturbances with anxiety. A total of 668 participants were recruited at sea level and 3700 m. The trials were performed at sea level (1 week prior to a 2-h flight to a high-altitude destination) and at 3700 m (24, 72, and 168 h). Sleep disturbances were assessed by self-reported sleep patterns and scores on the Athens Insomnia Scale (AIS). State anxiety was assessed using the Self-Rating Anxiety Scale (SAS). In our study, the incidence of sleep disturbances increased significantly after acute high-altitude exposure (65.3%, 434/668) and then gradually decreased after 72 h (50%, 141/282) and 168 h (44%, 124/282). The sleep assessments AIS [2.0 (4.0) vs. 4.0 (5.0)] and ESS [4.0 (4.0) vs. 5.0 (5.0)] increased significantly ( p < 0.05). Also, the SAS increased significantly from 26.25 (3.75) to 28.75 (7.5). The SAS was significantly high in sleep disturbance group [31.25 (7.5) vs. 27.5 (5), p < 0.001] than in the non-sleep- disturbance group. The baseline SAS and AIS scores were significantly higher in participants with sleep disturbances than in those without ( p < 0.01). Age, baseline insomnia, sleepiness, fatigue, and higher SAS were predictors of sleep disturbances in univariate regression (all p values < 0.05). However, only an older age ( p = 0.045) and a higher baseline SAS ( p = 0.018) remained independent predictors of sleep disturbances. Our findings indicated that acute high-altitude exposure triggers the onset of sleep disturbances, which are closely associated with anxiety. Furthermore, baseline state anxiety and age are independent predictors of sleep disturbances at high altitude.